Cerebrolysin, hemorrhagic transformation, and anticoagulation timing after reperfusion therapy in stroke: post hoc secondary analysis of the CEREHETIS trial - Kalinin, Mikhail N.; Khasanova, Dina R. (Frontiers in Pharmacology, 2026)
BackgroundThe optimal timing of anticoagulation resumption after acute ischemic stroke remains uncertain, particularly in patients at elevated risk of hemorrhagic transformation (HT). Although Cerebrolysin reduces HT incidence, its influence on dynamic HT risk and the safe anticoagulation window remains unclear.MethodsThis post hoc secondary survival analysis of the CEREHETIS trial (ISRCTN87656744) included 238 patients with intravenous thrombolysis (IVT)–treated middle cerebral artery (MCA) infarction. Patients were categorized into low (HTI 0) and high (HTI 1–4) HT-risk groups. Fourteen-day HT hazard trajectories were modeled using the Gompertz distribution. Nonlinear hazard acceleration (NLHA) and the compounding effect—reflecting self-amplifying instantaneous risk—were used to identify the inception point at which hazard stabilization may permit anticoagulation. A conservative NLHA threshold (0.23%–0.44%/day) defined this risk-equilibrium.ResultsIn high-risk patients, Cerebrolysin significantly reduced symptomatic HT (HR 0.245; 95% CI 0.072–0.837; p = 0.020) and any HT (HR 0.543; 95% CI 0.297–0.991; p = 0.032). In controls, the compounding effect peaked on day 1 and persisted into day 2, whereas Cerebrolysin attenuated this amplification and shortened the hazardous period. Inception points occurred on days 1–3 with Cerebrolysin vs. days 3–5 in controls. In low-risk patients, both groups reached stable hazard by day 2.ConclusionIn IVT-treated MCA stroke patients with HTI 1–4, Cerebrolysin may reduce HT hazard and advance the risk-equilibrium point by approximately 1–2 days. These findings are preliminary and hypothesis-generating, suggesting that Cerebrolysin may allow earlier—but individualized—anticoagulation resumption in selected high-risk patients, pending prospective validation.